"Our Blood Is Not Cheap": A Photovoice Project on Being Arab in a Racialized United States - Leticia Villarreal Sosa; Suhad Tabahi; Itedal Shalabi (Journal of Community Engagement and Scholarship)
The Arab American community has faced a history of racialization dating back to the late 19th century. The events of 9/11 and the heightened rhetoric of hate during the Trump presidency encouraged anti-Muslim sentiment and increased racial profiling and harassment. This community-based participatory research (CBPR) project uses Photovoice as a methodology to better understand the lived experiences and narratives of Arab Americans in the post-Trump1 era and as a tool for advocacy. The findings from the photo sharing sessions underscore the continued challenge of identity and representation, (in)visibility, and pushing back against anti-Arab/Muslim racism. The findings also highlight religion as a protective factor against structural and systemic racism. Overall, the participants in this study demonstrated their community resilience and navigational capital as they survived and thrived amid racializing experiences and microaggressions. Implications of this work include the need for increased consciousness raising about the lived experiences of the Arab American community and opportunities for allyship and advocacy.